2020
DOI: 10.1007/s11663-020-01917-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ternary Basicity of Iron Ore-Fluxed Pellets on Melting and Softening Properties in a Blast Furnace

Abstract: The cohesive zone is a region of low permeability in a blast furnace. This study shows the impact of the chemical composition of pellets on the metallurgical processes occurring in this region during the iron ore reduction process. Sixteen pellets containing varying contents of MgO, CaO, and SiO2 were investigated. The results indicate that increasing the MgO content of pellets improves their high-temperature properties; e.g., reduction degree and softening temperature. Modern equipment was used to replicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…When compared to studies by other researchers, no major contradictions were seen. Silva et al [3] studied sixteen pellets containing varying contents of MgO, CaO and SiO 2 . They concluded that increasing the pellets' MgO content leads to a higher softening temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to studies by other researchers, no major contradictions were seen. Silva et al [3] studied sixteen pellets containing varying contents of MgO, CaO and SiO 2 . They concluded that increasing the pellets' MgO content leads to a higher softening temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The cohesive zone is an area where ore starts to soften and melt; it has the highest resistance to gas flow, which leads to a high pressure drop over the cohesive zone. A narrow cohesive zone enables a smaller pressure drop and is favourable for BF operation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The melting-dropping properties of the charge directly determine the permeability of the blast furnace, thus affecting the fuel consumption and smelting efficiency in the blast furnace. [111][112][113] Therefore, the investigation of the effect of iron coke on the melting-dropping properties of the charge can provide a theoretical basis for the actual use of iron coke in the blast furnace. The melting-dropping properties of the charge mainly include softening property, melting property, dropping property, permeability, etc.…”
Section: Melting-dropping Properties Of the Chargementioning
confidence: 99%
“…It can be seen that MgO can improve the softening-melting property, while SiO 2 has the opposite effect. Silva et al 21) studied 16 pellets and analyzed the role of CaO and MgO in the pellets. The results showed that CaO and MgO promote the formation of dicalcium silicate and wustite and improve the melting point of the slag phase.…”
Section: Effect Of Sio 2 On the Softening-melting And Dropping Behavi...mentioning
confidence: 99%